Elevated systemic galectin-1 levels characterize HELLP syndrome. - Schnabel, Annegret (2016)
Galectin-1 (gal-1), a member of a family of conserved β-galactoside-binding proteins, has been shown to exert a key role during gestation. Though gal-1 is expressed at higher levels in the placenta from HELLP patients, it is still poorly understood whether systemic gal-1 levels also differ in HELLP patients. In the present study, we evaluated the systemic expression of gal-1, together with the angiogenic factors, placental growth factor (PlGF) and soluble fms-like tyrosine kinase 1 (sFlt-1) in conjunction with HELLP syndrome severity. Systemic levels of gal-1 and sFlt-1 were elevated in patients with both early- and late-onset HELLP syndrome as compared to healthy controls. In contrast, peripheral PlGF levels were decreased in early- and late-onset HELLP. A positive correlation between systemic gal-1 levels and sFlt-1/PlGF ratios was found in early onset HELLP patients. Our results show that HELLP syndrome is associated with increased circulating levels of gal-1; integrating systemic gal-1 measurements into the diagnostic analyses of pregnant women may provide more effective prediction of HELLP syndrome development